Physical activity and nutrition program for seniors (PANS): protocol of a randomized controlled trial - Burke, Linda; Jancey, Jonine; Howat, Peter; Lee, Andy; Kerr, Deborah; Shilton, T.; Hills, A.; Anderson, A. (BioMed Central Ltd, 2010)
Background: Along with reduced levels of physical activity, older Australian?s mean energy consumption hasincreased. Now over 60% of older Australians are considered overweight or obese. This study aims to confirm if alow-cost, accessible physical activity and nutrition program can improve levels of physical activity and diet ofinsufficiently active 60-70 year-olds.Methods/Design: This 12-month home-based randomised controlled trial (RCT) will consist of a nutrition andphysical activity intervention for insufficiently active people aged 60 to 70 years from low to medium socioeconomicareas. Six-hundred participants will be recruited from the Australian Federal Electoral Role and randomlyassigned to the intervention (n = 300) and control (n = 300) groups. The study is based on the Social CognitiveTheory and Precede-Proceed Model, incorporating voluntary cooperation and self-efficacy. The interventionincludes a specially designed booklet that provides participants with information and encourages dietary andphysical activity goal setting. The booklet will be supported by an exercise chart, calendar, bi-monthly newsletters,resistance bands and pedometers, along with phone and email contact. Data will be collected over three timepoints: pre-intervention, immediately post-intervention and 6-months post-study.Discussion: This trial will provide valuable information for community-based strategies to improve older adults?physical activity and dietary intake. The project will provide guidelines for appropriate sample recruitment, and thedevelopment, implementation and evaluation of a minimal intervention program, as well as information onminimising barriers to participation in similar programs.